2019
DOI: 10.1080/0144929x.2019.1571109
|View full text |Cite
|
Sign up to set email alerts
|

Creating collaborative groups in a MOOC: a homogeneous engagement grouping approach

Abstract: Collaborative learning can improve the pedagogical effectiveness of MOOCs.Group formation, an essential step in the design of collaborative learning activities, can be challenging in MOOCs given the scale and the wide variety in such contexts. We discuss the need for considering the behaviours of the students in the course to form groups in MOOC contexts, and propose a grouping approach that employs homogeneity in terms of students' engagement in the course. Two grouping strategies with different degrees of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 18 publications
0
36
0
1
Order By: Relevance
“…To support instructional designers in introducing collaboration, the literature has explored algorithmic approaches to group formation that can outperform random pairing. It has been found that groups formed by clustering of students using certain criteria yield less dropouts [15] and more social interactions [12] compared to the groups formed by random matching. [13] set up groups using theory-driven team formation principles (e.g., heterogeneity in knowledge supports creativity in the group), achieving more productive engagement.…”
Section: Background Collaborative Learning In Moocsmentioning
confidence: 99%
See 3 more Smart Citations
“…To support instructional designers in introducing collaboration, the literature has explored algorithmic approaches to group formation that can outperform random pairing. It has been found that groups formed by clustering of students using certain criteria yield less dropouts [15] and more social interactions [12] compared to the groups formed by random matching. [13] set up groups using theory-driven team formation principles (e.g., heterogeneity in knowledge supports creativity in the group), achieving more productive engagement.…”
Section: Background Collaborative Learning In Moocsmentioning
confidence: 99%
“…Consequently, peer interaction and support barely exist in MOOCs [9]. engagement and achievement of learners [15,12]. In the research on supporting collaborative learning in MOOCs, most works have focused on offering technological solutions to perform group formation automatically [12,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, the use of "learning analytics" allows the collection, measurement, analysis, and reporting of various MOOCs' learner data [21], and provides design data to have an attractive and interactive interface, problem/situation-based learning and complexity to promote self-efficacy and flexibility. Design is a critical factor in countering dropout [22], as well as integrating teaching strategies such as game-playing, social networking, and collaborative learning which become attractive to users [23][24][25].…”
Section: Introductionmentioning
confidence: 99%